2020
DOI: 10.1111/trf.15900
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative erythropoietin within a patient blood management program decreases both blood transfusion and postoperative anemia: a prospective observational study

Abstract: BACKGROUNDIn orthopedic surgery, a patient blood management program (PBM) has been proposed to reduce blood transfusion. The aim of this observational study was to assess, within a PBM, the specific efficacy of preoperative erythropoietin (EPO).STUDY DESIGN AND METHODSIn a single hospital, 723 patients undergoing elective primary hip or knee arthroplasty were prospectively studied. The PBM included EPO if preoperative hemoglobin was lower than 13 g/dL, intraoperative administration of tranexamic acid, use of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Females tended to have lower Hb levels before surgery; Steuber et al identified females accounting for 92% of patients with pre-operative iron deficiency anemia ( 18 ). Biboulet et.al found blood transfusion was more common in females through univariate analysis, though such significance disappeared in multivariate analysis ( 19 ). Another group of researchers obtained similar results that female patients were more likely to receive transfusion than males ( 20 ); thus, it’s reasonable that we included sex as one of the predictors in our nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Females tended to have lower Hb levels before surgery; Steuber et al identified females accounting for 92% of patients with pre-operative iron deficiency anemia ( 18 ). Biboulet et.al found blood transfusion was more common in females through univariate analysis, though such significance disappeared in multivariate analysis ( 19 ). Another group of researchers obtained similar results that female patients were more likely to receive transfusion than males ( 20 ); thus, it’s reasonable that we included sex as one of the predictors in our nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…1026 Additionally, an observational study of 723 patients undergoing elective primary hip or knee arthroplasty noted that inclusion of pre-operative EPO in the PBM programme (if pre-operative Hb <13 g dl À1 ) reduced the rate of blood transfusion and postoperative anaemia. 1027 Based on these and similar data, the international consensus statement on management of postoperative anaemia suggests considering the use of ESAs in noncancer patients with severe postoperative anaemia and inflammation-induced blunted erythropoiesis those declining blood transfusion. 1005 Current guidelines for PBM recommend a restrictive transfusion strategy for RBCs without specifying explicit Hb thresholds for the postoperative phase, but generally emphasising physiological RBC transfusion triggers (taking into consideration the patient's signs of organ ischaemia and the influence of pre-existing cardiovascular disease on the adequacy of cardiopulmonary reserve and tolerance to anaemia).…”
Section: Evidence Summarymentioning
confidence: 97%
“…Identifying a robust preoperative HB cutoff could offer opportunities for doctors to treatment patient’s anemia and decrease the PMSA risk. Patients whose preoperative HB was less than the cutoff value could receive intervention early, such as erythropoietin and iron supplementation, to avoid PMSA and associated complications [ 22 – 27 ].…”
Section: Discussionmentioning
confidence: 99%